Effect of using movies to enhance personal responsibility of university students - Chuchai Smithikrai (2018)
© 2015, Canadian Center of Science and Education. All right reserved. The objective of this study was to determine whether systematic movie-based training program can help developing personal responsibility in students. The research sample was 84 undergraduate students of a large public university in northern Thailand. Participants were randomly assigned to two experimental groups (movie+discussion and movie only) and one control group. Experimental group 1 and 2 viewed 5 movies which vividly portray personal responsibility during 5-weekly sessions. In addition, experimental group 1 participated in a 40-minute elaboration session about personal responsibility after viewing each movie. For the control group, participants received no intervention. Through a pretest, posttest control group experimental design, the two training groups experienced a significant increase in personal responsibility, while the randomly assigned control group showed no significant increase. In addition, results of the analysis of covariance indicated that systematic movie-based training positively developed personal responsibility, as the group variable predicted personal responsibility at post-training and 1-month follow-up periods while controlling for pre-training scores. Thus, the results of this experimental study provide support that personal responsibility can be enhanced through a five-period movie training intervention.